Meningkatkan Prestasi Belajar Mengapresiasi Dongeng Melalui Optimalisasi Sosiodrama - Saelendra, Ni Nyoman (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2016)
Learning achievement on Indonesian language was low, it became apprehensive for teachers. Through this research, teachers tried to improve Indonesian language learning achievement through best socio drama. Socio drama approach was believed that it could improve Indonesian language learning achievement. This research was conducted in two cycles. In this research, researcher used test and observation sheet, and data was analyzed by descriptive quantitative. Based on data analysis showed that learning achievement was increased in cycle I completeness was 23 students (69,7%) and not completeness was 10 students (30,3%), and in cycle II students completeness were 29 students (87,00%) and students who weren’t completeness were 4 students (12,1%). By improving mean score in cycle I 69,4 became 76,4 in cycle II. Implementing socio drama, teacher tried to conduct 10 steps in cycle I and it became improved in cycle II, based 13 steps on lesson plan. Based on the data of students’ achievement learning completeness 69,7% in cycle I became 89,7% in cycle II. The data of students’ socio drama activities in cycle I 60% increased in cycle II became 87%, so it could be stated that socio drama approach had been conducted with optimize and this learning could improve Indonesian language learning achievement. The result of this research could improve pedagogic services for teachers and could improve learning service quality for school. So that the result of research could be used for students to improve fairy tale appreciation, for teachers this research could improve learning services, for school could improve competitive ability.